Analysis of Floating Net Cages on The Carrying Capacity of The Darma Reservoir - tribhuwana, Awliya; Muttaqin, Zaenal; Farhan, Ohan (Jurnal Teknik Sipil dan Perencanaan, 2021)
Abstract. Darma Reservoir functions as a reservoir for irrigation, fisheries, and recreational and sports facilities. Currently, it only functions for irrigation and fish farming by floating net ponds. The development of floating net frameworks was so rapid that it conflicted with reservoir management. This study aims to determine the density of the floating net framework of the sedimentation conditions of the Darma Reservoir and to determine the development of the sedimentation rate of the Darma Reservoir in relation to the service life of the reservoir characterized by reduced dead storage. The first step was carried out by surveying the presence of the number of floating net cages, the distribution of the feed, the percentage of feed demand, the carrying capacity of the reservoir, then a topographic survey of the depth of the Darma reservoir to determine the capacity, rate and volume of sediment deposits. This study used quantitative approach, it began with distributing questionnaire forms and measuring the depth of the reservoir. The current condition of floating net cages is 4916 occupying 5.819% of the inundation area of 312.15 ha with an elevation of 712.50 m, while floating net cages are allowed according to the carrying capacity of Darma Reservoir waters amounting to 1,021. tons / harvest while the spawning pond is 3.483 tons/harvest. The volume of normal active storage for elevation 712.50 in 2020 is 28.086 million m3, while the volume of sediment deposits is 9.262 million m3 32.98%, the average sediment rate in the reservoir from 1988 to 2020 is 0.2894 million m3/year, while the sediment rate in catchment area Dam Dharma with an area of 23.5 km2 of 71.873 mm/year. Sedimentation in the Darma Reservoir has exceeded the limit of the base elevation of the reservoir, the elevation of the dead reservoir and the lowest elevation, but the reservoir is still functional. The planning life of the darma reservoir is up to 50 years, the suitability of the initial planning of operations in 1970 with operations until 2020.